The Need for Psycho-Spiritual History in Clinical Medicine - Padmanabhan, Vijayaraghavan (Clinical Medicine And Health Research Journal, 2023)
In diseases of the body where the pathogenesis is presumed to be a disorder of structure and/or function of one or more of its components, the psychological aspect of the patient is side-lined and the spiritual aspect is out of consideration. In the presence of negative thoughts, the way a patient responds to a given treatment can be below expectations. Such negative thoughts can be recognized by probing into the patient’s mental attitude. Similar is the adverse effect when the patient feels a lack of genuine love and understanding in one’s social circle. Not recognising the presence of negativity in a patient’s psycho-spiritual history can lead to inappropriate or ineffective treatment. Inclusion of psycho-spiritual history in clinical medicine leads to opening up of a hidden aspect of the patient’s problem, which when tackled has significant therapeutic potential.